Prairie Protector: student development of systems thinking habits in the context of agroecosystems - Ingram, Erin; Keshwani, Jenny (Frontiers in Education, 2023)
The Great Plains ecosystem offers an opportunity for young people to gain knowledge about intricate systems through practical learning. The spread of woody plants into grasslands, known as the "Green Glacier," poses a risk to biodiversity and animal production. Although effective management strategies exist, some land managers are reluctant to use them. To address such complex agroecosystem problems, it is critical to cultivate a scientifically literate population that can think systematically and make informed decisions based on STEM principles. Developing systems thinking abilities in learners is vital in enabling them to analyze and evaluate intricate systems like the Great Plains ecosystem. The study's objective was to determine whether Prairie Protector, an educational game, and its associated resources could help students acquire systems thinking habits. Based on the results, we concluded that researchbased educational games can be an effective tool for cultivating all 14 Habits of a Systems Thinker in high school students. Simulated environments that enable students to interact with complex systems should be explored further to promote their systems thinking skills.